EFFECTIVENESS OF AGILITY TRAINING IN PATIENST WITH ANTERIOR CRUCIATE LIGAMENT (ACL) INJURIES - Isdya Putri, Bernadine Felicia; Widodo, Agus; Mardianto, Halim (JTH: Journal of Technology and Health, 2025)
This study evaluates the importance of physiotherapy interventions in assisting patients to regain mobility and walking ability (ambulation) through agility training exercises. The study uses a case report method conducted on a 24-year-old male patient diagnosed with Post-Op ACL Reconstruction on the right knee (Dextra). The evaluations included measuring muscle strength using One Repetition Maximum (1 RM), assessing Range Of Motion (ROM) with a goniometer, conducting anthropometric measurements, and evaluating functional ability using the Lysholm Knee Scoring Scale (LKSS). The physiotherapy intervention consisted of agility training exercises, including ladder drills, cone drills, and hurdle drills. The ladder drills involved quick in-and-out movements within floor ladder boxes, the cone drills included running around cones arranged in specific patterns (zig-zag, T-drill, or 5-10-5), and the hurdle drills involved jumping over small obstacles (lateral hop, forward hop, quick step). The results showed that the strength of the left quadriceps was higher than the right based on the calculated 1 RM values, the left knee shows good recovery progress while the right knee still requires further intervention to improve its function in terms of range of motion (ROM), no significant changes were observed in the length from the tibial tuberosity to the proximal measurement points over time (T0 to T3), indicating stable dimensions during the observation period, and functional ability as assessed by LKSS was interpreted as good knee function, meaning the knee functioned well, daily activities were generally not significantly impaired, and there were minimal complaints.